2015
DOI: 10.2144/000114319
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Segmented Filamentous Bacteria from Complex Gut Microbiota

Abstract: Segmented filamentous bacteria (SFB) modulate the ontogeny of the immune system, and their presence can significantly affect mouse models of disease. Until recently, the inability to successfully culture SFB has made controlled studies on the mechanisms by which these bacteria exert their influence problematic. Here, we report a new method for selecting SFB from complex microbial mixtures, providing researchers a simple and cost-effective means to prepare pure infective inocula for prospective studies and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Single-cell sequencing demonstrated that single nucleotide polymorphism (SNP) mutations exist within disparate SFB genomes isolated from the same host (23). Current technology for SFB culture and passage in vitro is relatively unrefined (13,14). There are no simple single-cell sequencing methods available for detecting various SFB strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-cell sequencing demonstrated that single nucleotide polymorphism (SNP) mutations exist within disparate SFB genomes isolated from the same host (23). Current technology for SFB culture and passage in vitro is relatively unrefined (13,14). There are no simple single-cell sequencing methods available for detecting various SFB strains.…”
Section: Discussionmentioning
confidence: 99%
“…Ericsson et al and Schnupf et al established culturing methods for mouse SFB in vitro (13,14), although passaging of SFB in vitro is still problematic (13). Cultureindependent bioinformatic analysis could be used as a tool in finding candidate SFB functional genes.…”
mentioning
confidence: 99%
“…Experimental infection of susceptible Rainbow trout stock with feces from RTGE animals induced colonization and characteristic histopathological lesions containing SFB and an unidentified Gram-negative coccus, suggesting that SFB, in part, may be the etiological cause of RTGE ( McCarthy et al, 2016 ). Recent advances have identified different methods to culture SFB in vitro , accelerating research to study the interaction of SFB with different members of the intestinal microbiota ( Ericsson et al, 2015 ; Schupf et al, 2015 ).…”
Section: Effect On Host Microbiomementioning
confidence: 99%
“…Later on, SFB load decreases becoming stable in adult animals probably in relation to age-dependent maturation and activity of the immune system. 17 It is difficult to validate similar data in humans, with follow-up studies of children from weaning to adult age. However, Yin et al analysed fresh faecal samples 18 and showed that SFB colonisation is age dependent in humans with the majority of individuals colonised within the first 2 years of life, and also that this colonisation disappeared by the age of 3 years.…”
Section: Introductionmentioning
confidence: 99%